The Vestibular Implant: Hearing Preservation during Intralabyrinthine Electrode Insertion—A Case Report - van de Berg, Raymond; Lucieer, Florence; Guinand, Nils; van Tongeren, Joost; George, Erwin; Guyot, Jean-Philippe; Kingma, Herman; van Hoof, Marc; Temel, Yasin; van Overbeeke, Jacobus; Perez-Fornos, Angelica; Stokroos, Robert (Frontiers in Neurology, 2017)
Objective. The vestibular implant seems feasible as a clinically useful device in the near future. However, hearing preservation during intralabyrinthine implantation remains a challenge. It should be preserved to be able to treat patients with bilateral vestibulopathy and (partially) intact hearing. This case study investigated the feasibility of hearing preservation during the acute phase after electrode insertion in the semicircular canals. Methods. A 40-year old woman with normal hearing underwent a translabyrinthine approach for a vestibular schwannoma Koos Grade IV. Hearing was monitored using Auditory Brainstem Response Audiometry (ABR). ABR-signals were recorded synchronously to video recordings of the surgery. Following the principles of soft surgery, a conventional dummy electrode was inserted in the lateral semicircular canal for several minutes and subsequently removed. The same procedure was then applied for the posterior canal. Finally, the labyrinthectomy was completed and the schwannoma was removed. Results. Surgery was performed without complications. No leakage of endolymph and no significant reduction of ABR response were observed during insertion and after removal of the electrodes from the semicircular canals, indicting no damage to the peripheral auditory function. The ABR-response significantly changed when the semicircular canals were completely opened during the labyrinthectomy. This was indicated by a change in the morphology and latency of peak V of the ABR signal. Conclusion. Electrode insertion in the semicircular canals is possible without acutely damaging the peripheral auditory function measured with ABR, as shown in this proof-of-principle clinical investigation.